Principal Leadership in Improving Teacher Performance in Junior High Schools - Pagawak, Davison; Lengkong, Jeffry SJ; Krowin, Martinus (Abdurrauf Science and Society, 2025)
The purpose of this study was to analyze the function of the principal's leadership as a function or to direct in improving teacher performance. At State Junior High School 1 Kobakma, Central Mamberamo Regency. The approach used in this study is a qualitative descriptive approach with a case study research type. The results of the study stated that the principal had implemented leadership in improving teacher performance at State Junior High School I Kobakma well, the principal absorbed his leadership style which was democratic, straightforward, and open, prepared open time with the school community, emphasized teachers to be disciplined, held meetings with residents on topics that required special attention, teacher guidance and helped teachers to solve problems faced by teachers, directed teachers and provided training to teachers to improve their abilities, and increased class visits.